INTERVIEW WITH STEPHEN HUNT: Entrevista com Stephen Hunt - Duarte, José (2017)
We had the opportunity to interview Stephen Hunt for this special issue of Redisco. Stephen Hunt is an English fantasy, science fiction and thriller/crime author. His best-known works, the Jackelian series of fantasy novels, originally appeared in the UK, Canada, Australia, and New Zealand, through the Voyager imprint of HarperCollins and these novels are now published all around the world. He has a major new fantasy series – the Far-called Sequence – the first novel of which has now come out in 2014, called In Dark Service and published by Gollancz (an imprint of Orion Publishing and Hachette Livre). Website: http://stephenhunt.net.